CONTRIBUTION OF THE CARAVASILE FAMILY TO THE DEVELOPMENT OF CAHUL: A HISTORICAL PERSPECTIVE - Oleg M. Danilceac (Romanian Journal of Historical Studies)
The history of this family of owners is interesting because its representatives are part of the pleiad of the founders of Cahul fair. Starting with 1857, Cahul’s evolution is experiencing difficult moments, the danger of suspending its role as county administrative country center could fundamentally change its fate further. First, trade, the main source of development of the city, would have suffered. Cahul was at risk of becoming a transit point for agricultural goods and products from nearby villages. The Caravasile dynasty contributed considerably to the development of Cahul in general and southern Bessarabia in particular. At the present stage this topic becomes of considerable relevance, because it allows us to perceive in a new way the history of the socioeconomic development of Cahul. The research is based on documents from the National Archive, the Cahul Regional Museum, the Bucharest electronic library and the historical publications. Among the documents from the National Archive of the Republic of Moldova we highlight the correspondence of the officials of the Gubernial Construction Section Department to the Ismail Police Station. Among the documents from the fund of the Cahul County Museum, we mention the property certificate issued to Alexei Cara-Vasile. Historical documents from the Bucharest digital library inform us through Romania’s Official Gazette about the property of the Caravasile dynasty.